G protein diversity: a distinct class of alpha subunits is present in vertebrates and invertebrates. - Strathmann, M (1990)
Heterotrimeric guanine nucleotide-binding proteins (G proteins) are integral to the signal transduction pathways that mediate the cell's response to many hormones, neuromodulators, and a variety of other ligands. While many signaling processes are guanine nucleotide dependent, the precise coupling between a variety of receptors, G proteins, and effectors remains obscure. We found that the family of genes that encode the alpha subunits of heterotrimeric G proteins is much larger than had previously been supposed. These novel alpha subunits could account for some of the diverse activities attributed to G proteins. We have now obtained cDNA clones encoding two murine alpha subunits, G alpha q and G alpha 11, that are 88% identical. They lack the site that is ordinarily modified by pertussis toxin and their sequences vary from the canonical Gly-Ala-Gly-Glu-Ser (GAGES) amino acid sequence found in most other G protein alpha subunits. Multiple mRNAs as large as 7.5 kilobases hybridize to G alpha q specific probes and are expressed at various levels in many different tissues. G alpha 11 is encoded by a single 4.0-kilobase message which is expressed ubiquitously. Amino acid sequence comparisons suggest that G alpha q and G alpha 11 represent a third class of alpha subunits. A member of this class was found in Drosophila melanogaster. This alpha subunit, DG alpha q, is 76% identical to G alpha q. The presence of the Gq class in both vertebrates and invertebrates points to a role that is central to signal transduction in multicellular organisms. We suggest that these alpha subunits may be involved in pertussis toxin-insensitive pathways coupled to phospholipase C.